Physical characteristic of brown algae (Phaeophyta) from madura strait as irreversible hydrocolloid impression material - Prihartini Widiyanti; Siswanto Siswanto (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: Brown algae is a raw material for producing natrium alginates. One type of brown algae is Sargassum sp, a member of Phaeophyta division. Sargassum sp could be found in Madura strait Indonesia. Natrium alginate can be extracted from Sargassum sp. The demand of alginate in Indonesia is mainly fulfilled from abroad, meanwhile Sargassum sp is abundantly available. Purpose: The purpose of study were to explore the potency of brown alga Sargassum sp from Madura strait as hydrocolloid impression material and to examine its physical characteristic. Methods: The methods of research including extraction natrium alginate from Sargassum sp, synthesis of dental impression material and the test of porosity, density, viscosity, and water content of impression material which fulfilled the standard of material used in clinical application in dentistry. Results: Extraction result of Sargassum sp was natrium alginate powder with cream colour, odorless, and water soluble. The water content of natrium alginate was 21.64% and the viscosity was 0.7 cPs. The best porosity result in the sample with the addition of trinatrium phosphate 4% was 3.61%. Density value of impression material was 3 gr/cm3. Conclusion: The research suggested that brown algae Sargassum sp from Madura strait is potential as hydrocolloid impression material, due to its physical properties which close to dental impression material, but still need further research to optimize the physical characteristic.Latar belakang: Alga coklat adalah sumber bahan baku material natrium alginat. Salah satu jenis alga coklat adalah Sargassum sp yang merupakan anggota divisi Phaeophyta. Sargassum sp dapat ditemukan di Selat Madura Indonesia. Natrium alginat dapat diekstraksi dari Sargassum sp. Kebutuhan akan bahan ini di Indonesia sebagian besar dipenuhi dari impor, padahal ketersediaan Sargassum sp di Indonesia sangat melimpah. Tujuan: Penelitian ini bertujuan untuk mengeksplorasi potensi alga coklat Sargassum sp dari Selat Madura sebagai bahan cetak hidrokoloid dan meneliti karakteristik fisiknya. Metode: Tahap pertama adalah ekstraksi natrium alginat dari Sargassum sp, tahap kedua yaitu sintesis bahan cetak gigi dan menguji karakteristik bahan seperti porositas, densitas, viskositas, kadar air, bahan cetak yang memenuhi standar bahan yang digunakan dalam aplikasi klinis bidang Kedokteran Gigi. Hasil: Hasil ekstraksi berupa natrium alginat bubuk dengan warna krem, tidak berbau, dan dapat larut dalam air. Kadar air natrium alginat sebesar 21,64% dengan viskositas 0,7 cPs. Porositas terbaik dalam sampel dengan penambahan trinatrium fosfat 4% yaitu 3,61%. Nilai densitas bahan cetak 3 gr/cm3. Kesimpulan: Penelitian ini menunjukkan bahwa alga coklat Sargassum sp dari Selat Madura memiliki potensi sebagai bahan cetak hydrocolloid kedokteran gigi karena memiliki karakter fisik yang mirip dengan bahan cetak kedokteran gigi, namun masih memerlukan penelitian lebih lanjut untuk mengoptimalkan karakter fisiknya.